Non-Steroidal Anti-Inflammatory Drugs Increase Cisplatin, Paclitaxel, and Doxorubicin Efficacy against Human Cervix Cancer Cells - Diana Xochiquetzal Robledo-Cadena; Juan Carlos Gallardo-Pérez; Víctor Dávila-Borja; Silvia Cecilia Pacheco-Velázquez; Javier Alejandro Belmont-Díaz; Stephen John Ralph; Betsy Alejandra Blanco-Carpintero; Rafael Moreno-Sánchez; Sara Rodríguez-Enríquez (MDPI AG, 2020)
This study shows that the non-steroidal anti-inflammatory drug (NSAID) celecoxib and its non-cyclooxygenase-2 (COX2) analogue dimethylcelecoxib (DMC) exert a potent inhibitory effect on the growth of human cervix HeLa multi-cellular tumor spheroids (MCTS) when added either at the beginning ("preventive protocol"; IC50 = 1 ± 0.3 nM for celecoxib and 10 ± 2 nM for DMC) or after spheroid formation ("curative protocol"; IC50 = 7.5 ± 2 µM for celecoxib and 32 ± 10 µM for DMC). These NSAID IC50 values were significantly lower than those attained in bidimensional HeLa cells (IC50 = 55 ± 9 µM celecoxib and 48 ± 2 µM DMC) and bidimensional non-cancer cell cultures (3T3 fibroblasts and MCF-10A mammary gland cells with IC50 from 69 to >100 µM, after 24 h). The copper-based drug casiopeina II-gly showed similar potency against HeLa MCTS. Synergism analysis showed that celecoxib, DMC, and casiopeinaII-gly at sub-IC50 doses increased the potency of cisplatin, paclitaxel, and doxorubicin to hinder HeLa cell proliferation through a significant abolishment of oxidative phosphorylation in bidimensional cultures, with no apparent effect on non-cancer cells (therapeutic index >3.6). Similar results were attained with bidimensional human cervix cancer SiHa and human glioblastoma U373 cell cultures. In HeLa MCTS, celecoxib, DMC and casiopeina II-gly increased cisplatin toxicity by 41-85%. These observations indicated that celecoxib and DMC used as adjuvant therapy in combination with canonical anti-cancer drugs may provide more effective alternatives for cancer treatment.